2016
DOI: 10.5210/fm.v21i8.6752
|View full text |Cite
|
Sign up to set email alerts
|

LatinoTwitter: Discourses of Latino civic Engagement in social medie

Abstract: Twitter, like other social media platforms, has been identified as a space for cultural groups to debate political ideologies, engage civically, and even form action strategies for social change. Since 2014, the #LatinoTwitter hashtag has been used by Latino users for these purposes. Despite the popularity of the hashtag, few studies have examined it or its users. This study provides the results of a discourse analysis of the 31,000 tweets from 2014–2016 that use the hashtag. The findings indicate Twitter has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Such events include Donald Trump's racist discourse and the nativist hate crimes it has fomented in the U.S.; tensions over the use of the label "Latinx;" former NBC Nightly News anchor Tom Brokaw's description of Hispanics as predominantly Spanishspeaking and unassimilable; Beto O'Rourke and Cory Booker's use of the Spanishlanguage, seen as "hispandering," during one of the Democratic Party's 2019 debates; and Spanish-born recording artist Rosalía winning both a Latin Grammy and the 2019 VMA's "Best Latin" category. In tandem with this analysis, scholars such as Novak et al (2016) have identified four main discourses surrounding Latino use of Twitter, which include racial positionality in the U.S, social and civic protest and engagement, information sharing, and promotion of Latino products, persons, and brands.…”
Section: Theorizing Latinidad and Latinx Twittermentioning
confidence: 99%
“…Such events include Donald Trump's racist discourse and the nativist hate crimes it has fomented in the U.S.; tensions over the use of the label "Latinx;" former NBC Nightly News anchor Tom Brokaw's description of Hispanics as predominantly Spanishspeaking and unassimilable; Beto O'Rourke and Cory Booker's use of the Spanishlanguage, seen as "hispandering," during one of the Democratic Party's 2019 debates; and Spanish-born recording artist Rosalía winning both a Latin Grammy and the 2019 VMA's "Best Latin" category. In tandem with this analysis, scholars such as Novak et al (2016) have identified four main discourses surrounding Latino use of Twitter, which include racial positionality in the U.S, social and civic protest and engagement, information sharing, and promotion of Latino products, persons, and brands.…”
Section: Theorizing Latinidad and Latinx Twittermentioning
confidence: 99%